Ambulatory blood pressure monitoring, European guideline targets, and cardiovascular outcomes: an individual patient data meta-analysis - Zhang, Dong-Yan; An, De-Wei; Yu, Yu-Ling; Melgarejo, Jesus D; Boggia, José; Martens, Dries S; Hansen, Tine W; Asayama, Kei; Ohkubo, Takayoshi; Stolarz-Skrzypek, Katarzyna; Malyutina, Sofia; Casiglia, Edoardo; et al. (European heart journal, 2025)
BACKGROUND AND AIMS: Hypertension is the predominant modifiable cardiovascular risk factor. This cohort study assessed the association of risk with the percentage of time that the ambulatory blood pressure (ABP) is within the target range (PTTR) proposed by the 2024 European Society of Cardiology (ESC) guidelines for blood pressure (BP) management. METHODS: In a person-level meta-analysis of 14 230 individuals enrolled in 14 population cohorts, systolic and diastolic ABPs were combined to assess 24-h, daytime, and nighttime PTTR with thresholds for non-elevated ABP set at <115/65, <120/70, and <110/60 mmHg, respectively. RESULTS: Median 24-h PTTR was 18% (interquartile range 5-33) corresponding to 4.3 h (1.2-7.9). Over 10.9 years (median), deaths (N = 3117) and cardiovascular endpoints (N = 2265) decreased across increasing 24-h PTTR quartiles from 21.3 to 16.1 and from 20.3 to 11.3 events per 1000 person-years. The standardized multivariable-adjusted hazard ratios for 24-h PTTR were 0.57 (95% confidence interval 0.46-0.71) for mortality and 0.30 (0.23-0.39) for cardiovascular endpoints. Analyses of daytime and nighttime ABP, cardiovascular mortality, coronary endpoints and stroke, and subgroups produced confirmatory results. The 2024 ESC non-elevated 24-h PTTR, compared with the 2018 ESC/European Society of Hypertension non-hypertensive 24-h PTTR, shortened the interval required to reduce relative risk for adverse outcomes from 60% to 18% (14.4-4.3 h). Office BP, compared with 24-h PTTR, misclassified most participants with regard to BP control. CONCLUSIONS: Longer time that ABP is within the 2024 ESC target range is associated with reduced adverse outcomes; PTTR derived from ABP refines risk prediction and compared with office BP avoids misclassification of individuals with regard to BP control.
Keywords: Risk stratification; Population science; Guidelines; Morbidity; Ambulatory blood pressure; Mortality